Robert Lucas, Nobel Prize of Economics 1995. How an historian became the most important economist of the Twentieth Century - Fernández-Baca, Jorge (1996)
Robert Lucas is the economist whose work has had the greatest impact on the development of macroeconomics in the present century. His contribution to macroeconomics is concentrated in three particular topics: the application of the rational expectations hypothesis, the emergence of an equilibrium theory of business cycles, and the econometric evaluation of economic policy. Lucas has also made major contributions to several other fields of economics such as finance and the theory of economic growth.